Pro-Inflammatory Properties of Salivary Gland-Derived Fibroblasts—Implications in Sjögren’s Disease - Matthias Brunner; Daniel Guggisberg; Marco Sprecher; Ondrej Pastva; Kristina Bürki; Miranda Houtman; Marco Kreuzer; Sara Andrea Krättli; Laura Jahnke; Mila Roceri; Rémy Bruggmann; Muriel Elhai; et al. (Cells)
Salivary gland dysfunction is a hallmark of Sjögren’s disease (SjD). Here, we investigated the pro-inflammatory properties of salivary gland-derived fibroblasts (SGF) that were cultured from minor salivary gland (MSG) tissues of patients with SjD and controls. SGF from patients with SjD exhibited higher rates of proliferation compared to controls. RNA sequencing revealed pronounced pro-inflammatory properties of SGF in response to stimulation with IL1 and polyI:C, with an activation of “interferon responses”, “JAK STAT”, and “NF-kappa B” signaling, as well as ”complement” pathways. In addition to encoding pro-inflammatory transcripts, stimulated SGF featured increased expression of a number of non-coding enhancer RNAs (eRNAs) that we originally identified in TNF-stimulated synovial fibroblasts (FLS) by CAGE sequencing. We confirmed the expression of selected eRNAs in SGF and FLS through time-course experiments upon stimulation with different pro-inflammatory stimuli using real-time PCR. Furthermore, we detected eRNAs for IL6 (eIL6) and IL8 (eIL8#3) in MSG tissues. Treatment of SGF with the bromodomain inhibitor I-BET suppressed IL1- and LPS-induced expression of all eRNAs tested, as well as their associated pro-inflammatory coding transcripts. Transfection of SGF with antisense nucleotides targeting eCCL20 reduced the LPS-induced expression of this eRNA, as well as CCL20 expression and secretion. Together, our data highlight similarities between SGF and FLS regarding their activation under inflammatory conditions.